Carbon monoxide clean-up of reformate gas by preferential oxidation - Muziki, Sibongile (Department of Chemical Engineering, 2016)
The preferential oxidation (PrOx) activity of two Ru/Al2O3 catalysts prepared using different methods was tested. The first catalyst was prepared by wetness impregnation at a high pH and the second was prepared by incipient wetness impregnation. Catalytic activity was measured at varying temperatures, space velocities as well as O2/CO ratio. The Ru catalyst catalyst prepared using wetness impregnation at high pH was found to exhibit higher CO conversion despite having a lower Ru dispersion compared to the Ru catalyst prepared using incipient wetness impregnation at the tested temperature range. For both Ru catalysts the trends observed with varying temperature, space velocity as well as O2/CO ratio were similar. Increasing temperature increased CO conversion up to a maximum after which a further increase in temperature led to a decrease in CO conversion. At low temperatures, increasing space velocity resulted in a decrease in CO conversion. An increase in CO conversion was observed with increasing space velocity at higher temperatures. Increasing space velocity led to a decrease in CH4 formation at high temperatures. Furthermore it was determined that mass transfer limitations played a role during the catalytic process. The effects of mass transfer limitations could be reduced by increase the linear space velocity. A Pt-Fe/mordenite catalyst was prepared in this study using solid state ion exchange to deposit Fe and competitive ion exchange to deposit Pt. This method was proposed in order to try and improve the preparation method reported in literature. The synthesised catalyst did not perform as well as the Pt-Fe/Mordenite reported in literature. A maximum CO conversion of 99 % with 47 % CO2 selectivity at 180 °C, 120 000 ml/(h gcat) and O2/CO ratio of 1 was achieved.